A Case of Pseudomonas Orbital Cellulitis Following Glaucoma Device Implantation. Issue 1 (January 2019) - Goldfarb, Jeremy; Jivraj, Imran; Yan, David; DeAngelis, Dan
Abstract : Purpose: Orbital cellulitis is a rare complication of aqueous tube shunt surgery. Nine cases have been described in the literature, though the microbiologic etiology is rarely reported. Management with intravenous antibiotics and/or explantation has been described. Methods: This is a case report and literature review. Case: A 64-year-old woman developed pain, periorbital swelling, limited extraocular motility, proptosis, and conjunctival injection 3 days following implantation of an Ahmed Glaucoma Valve. Computed tomography of the orbits with contrast showed soft tissue fat stranding consistent with orbital inflammation. Initial medical management with topical and intravenous ceftriaxone and vancomycin was unsuccessful. Surgical removal of the implant was performed and intraoperative cultures demonstrated florid Pseudomonas aeruginosa growth. Antibiotic coverage was changed to Piperacillin-Tazobactam for 3 days, with eventual resolution of her orbital symptoms. Conclusions: We report the first case of orbital cellulitis after implantation of a glaucoma device associated with P. aeruginosa . Failure of intravenous and topical antibiotics led to explantation of the valve and targeted intravenous antibiotic therapy with subsequent clinical improvement.